Insights into Ongoing Evolution of the Hexachlorocyclohexane Catabolic Pathway from Comparative Genomics of Ten Sphingomonadaceae Strains. Issue 6 (1st June 2015) - Pearce, Stephen L; Oakeshott, John G; Pandey, Gunjan
Abstract: Hexachlorocyclohexane (HCH), a synthetic organochloride, was first used as a broad-acre insecticide in the 1940s, and many HCH-degrading bacterial strains have been isolated from around the globe during the last 20 years. To date, the same degradation pathway (the lin pathway) has been implicated in all strains characterized, although the pathway has only been characterized intensively in two strains and for only a single HCH isomer. To further elucidate the evolution of the lin pathway, we have biochemically and genetically characterized three HCH-degrading strains from the Czech Republic and compared the genomes of these and seven other HCH-degrading bacterial strains. The three new strains each yielded a distinct set of metabolites during their degradation of HCH isomers. Variable assembly of the pathway is a common feature across the 10 genomes, eight of which (including all three Czech strains) were either missing key lin genes or containing duplicate copies of upstream lin genes ( linA-F ). The analysis also confirmed the important role of horizontal transfer mediated by insertion sequence IS6100 in the acquisition of the pathway, with a stronger association of IS6100 to the lin genes in the new strains. In one strain, a linA variant was identified that likely caused a novel degradation phenotype involving a shift in isomer preference. This study identifies a number of strains that are in the early stages of lin pathway acquisition and shows that the state of the pathway can explain the degradation patterns observed.